21 Effect of data quality improvement intervention on health management information system data accuracy: an interrupted time series analysis. (25th November 2019) - Mulissa, Zewdie; Wendrad, Naod; Bitewulign, Befikadu; Biadgo, Abera; Abate, Mehiret; Alemu, Haregeweyni; Abate, Biruk; Kiflie, Abiyou; Magge, Hema; Parry, Gareth
Abstract : Background: As part of a partnership between the Institute for Healthcare Improvement and Ethiopian Federal Ministry of Health (FMoH), a Maternal and Neonatal Health (MNH) Collaborative took place between November 2016 and December 2017 aiming to accelerate reduction of maternal and neonatal mortality in Lemu Bilbilu, Tanqua Abergele and Duguna Fango districts. Before starting the MNH Collaborative, assessments found inaccuracies in core process and outcome data obtained from Health Management Information System (HMIS) reports. Objectives: We aimed to assess the effect of an initiative to improve data quality in the MNH Collaborative. Methods: Building on the core MNH Collaborative design, data quality improvement activities were added. We used the WHO review methodology to derive a verification factor (VF) for the core measures of number of pregnant women that received antenatal care first visit, number of pregnant women that received antenatal care on at least four visits, number of pregnant women tested for syphilis and number of births attended by skilled health personnel. Impact was assessed using interrupted time series. Results: Data quality improved across all measures, for example, in Duguna Fango, the VF for number of pregnant women that received antenatal care first visit improved from 0.79 (quartiles 0.73, 0.85) pre-intervention to 0.99 (0.93, 1.00) post intervention, p<0.001; and the VF for number of pregnant women tested for syphilis increased from 0.45 (0.36, 0.48) to 0.96 (0.89, 0.99), p<0.001. Conclusions: A data quality improvement initiative significantly improved accuracy of data used to monitor maternal progress of this MNH Collaborative in Ethiopia.